Reassessment of diagnostic criteria in cutaneous lymphocytic infiltrates - Cotta, Ana Cristina (2004)
CONTEXT: Non-specific lymphocytic infiltrates of the skin pose difficulties in daily practice in pathology. There is still a lack of pathognomonic signs for the differential diagnosis between benign and malignant lymphocytic infiltrates. OBJECTIVE: To evaluate the morphological and immunohistochemical profile of lymphocytic infiltrations of the skin according to clinical outcome. TYPE OF STUDY: Retrospective; histopathological and immunohistochemical analysis. SETTING: Referral center, university hospital. SAMPLE: 28 cases of lymphocytic infiltrates of difficult differential diagnosis selected from the records. MAIN MEASUREMENTS: Eighteen histological variables and the immunophenotypic profile were assessed using the CD4, CD8, CD3, CD20 and CD30 lymphoid markers and compared to subsequent follow-up. RESULTS: The most common diagnoses were: initial mycosis fungoides (eight cases) and drug reactions (five cases). Single morphological variables did not discriminate between benign and malignant infiltrates except for the presence of Pautrier-Darier’s microabscesses, which were found only in mycosis fungoides (p = 0.015). Patterns of superficial and deep infiltration (p = 0.037) and also the presence of eosinophils (p = 0.0207) were more frequently found in benign lymphocytic infiltrates. Immunohistochemical profile of T-cell subsets showed overlap between benign and malignant infiltrates with a predominance of CD4-positive (helper) lymphocytes in the majority of cases. CONCLUSIONS: A combination of clinical and histological features remains the most reliable approach for establishing a definite diagnosis in cases of lymphoid skin infiltrates.